The Effect of Eco-Efficiency, Sustainability Reporting, and Dividend Policy on the Value of Mining Companies Listed on the Indonesian Stock Exchange - Surianti, Meily; Nasier, Nazwa; Ratna; Gultom, Selfi Afriani (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2025)
Firm value reflects market confidence and long-term corporate sustainability, particularly in environmentally sensitive industries such as mining. This study aims to examine the effect of eco-efficiency, sustainability reporting, and dividend policy on the firm value of mining companies listed on the Indonesia Stock Exchange during the 2021–2024 period. Using secondary data from annual and sustainability reports, this study analyzes 56 observations from 14 companies selected through purposive sampling. Panel data regression analysis is employed to test the proposed relationships. The results indicate that eco-efficiency, sustainability reporting, and dividend policy have insignificant effects on firm value, with eco-efficiency and dividend policy exhibiting negative relationships. These findings suggest that sustainability practices and dividend decisions have not yet been fully perceived by the market as value-enhancing factors. Therefore, mining companies need to strengthen the quality of environmental initiatives, sustainability disclosures, and financial policies to enhance firm value.